(untitled) (Revista Educação, Artes e Inclusão, 2023)
The approval of the International Convention on the Rights of Persons with Disabilities (CRPD) by Brazil in 2008, with the status of a constitutional amendment, established the legislative framework that should guide the elaboration of policies and laws in order to promote, protect and ensure the exercise of full and equitable access to all human rights and fundamental freedoms by all persons with disabilities and to promote respect for their inherent dignity. In this sense, the promulgation of the Statute of Persons with Disabilities (EPD) in 2015, committed to the effectiveness and effectiveness of the CRPD. It happens that access to education is a formal guarantee whose effectiveness is linked to the promotion of means proportionate and appropriate to the circumstances of the child and adolescent with ASD, in order to guarantee the development of their autonomy, to the greatest extent possible. In view of this, considering only early childhood education and elementary education, whose competence was assigned primarily to the municipalities, it is proposed to analyze Municipal Law nº. nº 3.833, in order to verify its suitability for the stated purposes of the CRPD and the EPD with regard to children and adolescents with ASD.